Democracy and national destinies on Taiwan. Issue 4 (26th July 2016) - Phillips, Steven
Abstract: In the case of Taiwan, experts have debated whether passionate national loyalties (Taiwanese or Chinese) facilitated or stymied democratization. This paper argues that nationalism facilitated political change in Taiwan. In fact, democratization during the 1980s and the 1990s was spurred in part by the pursuit of two conflicting national destinies. The Chinese Nationalist Party legitimized reform as the end of a century‐long process for the reconstruction of the Chinese nation. To many Nationalists, particularly those born on the mainland, Taiwan was the fulfilment of Sun Yat‐sen's vision of China known as the Three Principles of the People. At the same time, many opponents of the regime saw successful reform as one step towards the realization of a Taiwanese nation. Dominated by those who identified themselves as Taiwanese, generally those of Chinese descent whose ancestors had lived on Taiwan prior to 1945, these activists hoped to take power through the ballot box, then implement a series of policies to strengthen an island‐wide identity.